Power-laws f(R) theories are cosmologically unacceptable - Amendola, Luca; Polarski, David; Tsujikawa, Shinji (Arxiv, 2007)
In a recent paper [1] (PRL 98,131302,2007) we have shown that f(R)=R + mu R^{n} modified gravity dark energy models are not cosmologically viable because during the matter era that precedes the accelerated stage the cosmic expansion is given by a sim t^{1/2} rather than a sim t^{2/3}, where a is a scale factor and t is the cosmic time. A recent work [2] (PLB 639,135-143,2006) by Capozziello et al. criticised our results presenting some apparent counter-examples to our claim in f(R)= mu R^{n} models. We show here that those particular R^{n} models can produce an expansion as a sim t^{2/3} but this does not connect to a late-time acceleration. Hence, though acceptable f(R) dark energy models may exist, the R^{n} models presented in Capozziello et al. are not cosmologically viable, confirming our previous results in Ref. [1].